Media Sosial dan Game Online sebagai Transformasi dan Pencapaian Sosial: Perspektif Filsafat Etika - Ardi Tri Yuwono; Andi Sebastian; Pieter-Jan Clumpers (Danudirja Setyabudi Nusantara, 2026)
This study aims to critically analyze social media and online games as agents of social transformation and as spaces for achievement, using the ethical philosophy framework of Cal Newport, Byung-Chul Han, Ziauddin Sardar, and Carl Honoré, and to formulate ethical implications for a more meaningful digital life. The research method used is a qualitative approach with a conceptual analysis design rooted in philosophical thinking and cultural studies. The results of the study highlight that the social transformation triggered by social media and online games occurs in four dimensions: (1) Transformation of interactions that lose negativity; (2) Identity transformation that is algorithmically constructed with Western cultural biases; (3) The transformation of public space that shifts from deliberation to attention extraction, as well as; (4) The transformation of time that accelerates and erodes contemplation. Simultaneously, the meaning of achievement in the digital ecosystem is reduced to illusory virtual symbols, trapping individuals in self-exploitation, cultural homogenization, and loss of appreciation for process. The synthesis of the four perspectives gives birth to Digital Flourishing Ethics. This integral ethical framework combines the dimensions of focus, contemplation, epistemic-cultural, and temporal as normative alternatives in responding to the digital crisis. The implications of these findings provide insight into the need to redefine achievement, develop digital literacy, and implement regulations that protect cultural diversity and digital free spaces.